KEANEKARAGAMAN JENIS TUMBUHAN BERPOTENSI MENJADI TANAMAN HIAS PADA KAWASAN HUTAN LINDUNG GUNUNG BAWANG KABUPATEN BENGKAYANG - marega, .; Indrayani, Yuliati; Ardian, Hafiz (Universitas Tanjungpura, 2016)
The area of Gunung Bawang Protected Forest has diverse natural resources. One of them is the potential ornamental plant. This research aims to reveal the diversity of plants that could potentially be ornamental plants in the area of Gunung Bawang Protected Forest.This research was conducted with a survey method by taking sample plots of Wittaker 20 x 50 m as many as 10 plots of observation. Based on the research, the area of Gunung Bawang Protected Â Forest had 23 species of plants that could potentially be ornamental plants, namely Caladiuim sp, Cordiglotti sfiliformis, Drynaria sparsisora, Appendicula torta, Alocasiaplumbea â€whiteâ€™â€™, Liparis compressa, Bulboppylum sp, Thecopus sp, Thecostele sp, Bulbophyllum lobii, Dendrobium smithiaanum, Phalaenopsis sp, Coelogyne foerstermannii, Asplenium nidus, Oberonia ciliolata, Hermamolena sp, Alocasia inornata, Alocasia sp, Alocasia â€˜â€™tigrina superbaâ€™â€™, Anthurium sp, Alocasia culionensis, Flickingeria sp dan Spathoglottis plicata. There needs to be improvement of knowledge and awareness among the community about the existence and spesies of plants thet potentially become ornamental plants, because it is one of the sources of germ plasm so as to ensure its sustainability. Keywords: Biodiversity, Diversity, Gunung Bawang Protected Forest, Ornamental Plants